Promising medicinal plant Inula viscosa L.: antiproliferative, antioxidant, antibacterial and phenolic profiles - Ozkan, Erva; Pehlivan Karakas, Fatma; Birinci Yildirim, Arzu Birinci; Tas, Isa; Eker, Ismail; Zeynep Yavuz, Muhsine; Ucar Turker, Arzu (Progress in Nutrition, 2019)
Introduction. Inula viscosa (L.)  Aiton (sticky fleabane) is popular medicinal plant in the family Asteraceae. It has been used in traditional medicine in the treatment of cancer, diabetes, hypertension, bronchitis, tuberculosis, wounds, skin diseases, infertility, lung and gastro-duodenal disorders. Methods. Aim of this study was to evaluate in vitro antiproliferative, antioxidant and antibacterial activities of aqueous and methanol extracts of aerial parts of I. viscosa and their phenolic constituents. Antiproliferative activity was evaluated against human breast adenocarcinoma (MCF-7) and human brain cancer (T98-G) cell lines using MTT assay. Antioxidant activity was revealed by using 2,2-diphenyl-1-picrylhydrazil (DPPH) method. Total phenol and flavonoid were determined by using Folin-Ciocaltaeu and aluminum chloride (AlCl3) colorimetric method, respectively. The disc diffusion assay was used to screen for antibacterial activity against 10 bacteria. Phenolic constituents were detected by High Performance Liquid Chromatography-Diode-Array Detector (HPLC-DAD) via chosen ten phenolic molecules (gallic acid, caffeic acid, rutin, luteolin, kaempferol, rosmarinic acid, myricetin, quercetin, coumarin and apigenin). Results. Methanol extract of I. viscosa demonstrated better antiproliferative activity than aqueous extract against MCF-7 and T98-G cell lines. Strong DPPH radical scavenging activity was observed with both extracts. Total phenol and flavonoid content of methanol extract were twice as much as aqueous extract. Only Gram-positive bacteria (S. aureus, S. epidermidis and S. pyogenes) were inhibited by both extracts of I. viscosa. HPLC-DAD analysis of phenolic compounds revealed that I. viscosa was significant source of kaempferol. Conclusion: I. viscosa showed promising antibacterial, antioxidant and anticancer activities, and further studies should be conducted to isolate the active components.